2020
DOI: 10.1101/2020.03.13.989558
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genome-wide Screens Identify Lineage- and Tumor Specific-Genes Modulating MHC-I and MHC-II Immunosurveillance in Human Lymphomas

Abstract: Keywordsdiffuse large B-cell lymphoma, antigen presentation, MHC class I, MHC-I, MHC class II, immunotherapy, immunoevasion, EZH2, SUGT1, thymidylate synthase EZH2 and thymidylate synthase, enhances DLBCL MHC-I presentation. These and other genes represent potential targets for manipulating MHC-I immunosurveillance in cancers, infectious diseases, and autoimmunity.

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 77 publications
3
3
0
Order By: Relevance
“…Consistent with our findings, recent reports linked PRC2 to the control of expression of HLA molecules and other immune-related molecules in solid tumors and lymphomas [17][18][19] . Specifically, the catalytic subunit of PRC2, EZH2, has emerged as a potent regulator of antigen presentation in genome-wide screenings 18,19 , its mutations have been associated with impaired HLA expression in diffuse large B-cell lymphomas 17 , and overexpression of PRC2 in solid tumors has been shown to drive the transcriptional downregulation of HLA class I 18 .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Consistent with our findings, recent reports linked PRC2 to the control of expression of HLA molecules and other immune-related molecules in solid tumors and lymphomas [17][18][19] . Specifically, the catalytic subunit of PRC2, EZH2, has emerged as a potent regulator of antigen presentation in genome-wide screenings 18,19 , its mutations have been associated with impaired HLA expression in diffuse large B-cell lymphomas 17 , and overexpression of PRC2 in solid tumors has been shown to drive the transcriptional downregulation of HLA class I 18 .…”
Section: Discussionsupporting
confidence: 93%
“…Consistent with our findings, recent reports linked PRC2 to the control of expression of HLA molecules and other immune-related molecules in solid tumors and lymphomas [17][18][19] . Specifically, the catalytic subunit of PRC2, EZH2, has emerged as a potent regulator of antigen presentation in genome-wide screenings 18,19 , its mutations have been associated with impaired HLA expression in diffuse large B-cell lymphomas 17 , and overexpression of PRC2 in solid tumors has been shown to drive the transcriptional downregulation of HLA class I 18 . It has also been reported that EZH2 inhibition can result in derepression of endogenous retroviruses (ERVs), which can significantly contribute to boosting antitumor responses both by serving as antigens and through the induction of interferon responsive genes 20,21 .…”
Section: Discussionsupporting
confidence: 93%
“…Thus, this single genetic map identified components of the HLA-I pathway previously discovered through decades of research. In addition, HLA-I regulators identified in human B cell lymphoma CRISPR-Cas9 screens by Dersh et al, such as SUSD6, SND1, ANKRD33B, and EZH2, were confirmed as highly significant hits in our haploid genetic screen (Dersh et al, 2020). The most prominent hit from our screen in the W6/32 lo -sorted population was the gene encoding SPPL3, a protease that had not been previously described in the context of antigen presentation (Figure 1B).…”
Section: A Haploid Genetic Screen Provides a High-resolution Map Of The Hla-i Antigen Presentation Pathwaysupporting
confidence: 71%
“…In this situation, the reactive nitrogen species cause nitrosylation of residues in the MHC I peptide binding site, which can inhibit the binding of peptides (231). In tumor-bearing mice, myeloid suppressor cells cause defective IFN responses in host cells (responses in tumors were not examined) likely due to a STAT1 defect potentially caused by nitrosylation (232).…”
Section: Loss Of the Mhc I Antigen Presentation Pathway In Cancers Dumentioning
confidence: 99%